CLINICAL STUDY OF THE TRANSVERSA SITUATION IN THE INPROMI - Muñóz Sánchez, Julio (2015)
We studied 40 cases of situation Transverse found from a total of 8,957 births in the INPROMI since the start of the attention the April 20, 1971 until June 30, 1975, giving an incidence of 0.45%. Advanced age, multiparity and insufficient prenatal care were found in high percentage. Caesarean section as a method of uterine evacuation was performed in 82.5%. Prematurity reached 27% and hospital perinatal mortality, 7.5%. As factors, etiologic were recorded, Placenta Previa (15%). Cord dystocia (12.5%) and a narrow pelvis (5%). Overall maternal and neonatal morbidity what was high.